PENGARUH LEGALITAS HAK KOMUNAL HUTAN ADAT DI PULAU BARASAK, DESA PILANG, KECAMATAN JABIREN RAYA, KABUPATEN PULANG PISAU TERHADAP KELESTARIAN HUTAN ADAT - Misrita Misrita; Yetrie Ludang; Risa Masdania; Imam Qalyubi; Herry Palangka Jaya (Agrienvi: Jurnal Ilmu Pertanian, 2020)
This research was conduct to see the effect of the legality of hutan adat in Pilang Village Jabiren Raya Subdistrict Pulang Pisau District after the government inaugurated as a hutan adat on its preservation and to examine the factors that influence its sustainability and destruction. The design used in this research is descriptive qualitative with the purposive sampling method. To support the credibility in this study uses the data triangulation method. Based on data collection and data analysis carried out, it's finding that the legality of the communal rights of hutan adat on Barasak island shows that the community has awareness in maintaining and preserving hutan adat. Some of the factors behind the people's knowledge in protecting hutan adat include: because hutan adat themselves have benefits for the survival of indigenous, social, religious, economic, and cultural communities. For these reasons, the existence of hutan adat is still maintained and protected by the surrounding community. Keywords: hutan adat, legality, communal rights